Up-Scale Synthesis of p-(CH2-CH)C6H4CH2CH2CH2Cl and p-ClC6H4SiR3by CuCN-Catalyzed Coupling Reactions of Grignard Reagents with Organic Halides - Park, Ju Yong; Ko, Ji Hyeong; Lee, Hyun Ju; Park, Jun Hyeong; Lee, Junseong; Sa, Seokpil; Shin, Eun Ji; Lee, Bun Yeoul (ACS Omega, 2022)
Grignard reagents featuring carbanion characteristics are mostly unreactive toward alkyl halides and require a catalyst for the coupling reaction. With the need to prepare p-(CH2-CH)C6H4CH2CH2CH2Cl on a large scale, the coupling reaction of p-(CH2-CH)C6H4MgCl with BrCH2CH2CH2Cl was attempted to screen the catalysts, and CuCN was determined to be the best catalyst affording the desired compound in 80% yield with no formation of Wurtz coupling side product CH2-CHC6H4-C6H4CH-CH2. The p-(CH2-CH)C6H4Cu(CN)MgCl species was proposed as an intermediate based on the X-ray structure of PhCu(CN)Mg(THF)4Cl. p-ClC6H4MgCl did not react with sterically encumbered R3SiCl (R = n-Bu or n-octyl). However, the reaction took place with the addition of 3 mol % CuCN catalyst, affording the desired compound p-ClC6H4SiR3. The structures of p-(CH2-CH)C6H4CH2CH2CH2MgCl and p-ClC6H4MgCl were also elucidated, which existed as an aggregate with MgCl2, suggesting that some portion of the Grignard reagents were possibly lost in the coupling reaction due to coprecipitation with the byproduct MgCl2. R3SiCl (R = n-Bu or n-octyl) was also prepared easily and economically with no formation of R4Si when SiCl4 was reacted with 4 equiv of RMgCl. Using the developed syntheses, [p-(CH2-CH)C6H4CH2CH2CH2]2Zn and iPrN[P(C6H4-p-SiR3)2]2, which are potentially useful compounds for the production of PS-block-PO-block-PS and 1-octene, respectively, were efficiently synthesized with substantial cost reductions.